Identifikasi Kegiatan Program Kampung Keluarga Berencana di Kabupaten Aceh Tengah - Syahnur, Sofyan; Diantimala, Yossi; Ilham, Ridha (JPPUMA Jurnal Ilmu Pemerintahan dan Sosial Politik Universitas Medan Area, 2019)
The purpose of this study identified the activities of the Family Planning Village Population, Family Planning and Family Development program in Middle Aceh District. The study location were grouped according to the Geographic Difficulties Index of the Central Bureau of Statistics. Research data collection uses qualitative methods, namely interviews, documentation, and observations with the Village Head / Geuchik (informant 1), extension / coach of the Family Planning Village (informant 2), and management of the Family Planning Village (informant 3). The results of this study indicate that the implementation of family planning village activities in the village is of high difficulty and is not difficult geographically has been relatively active, namely the management and mentor and companion of the family planning village to work well and directed, while the villages with moderate difficulty level geographically less active. Generally, the activities of the Family Planning Village carried out are posyandu, posbindu, elderly gymnastics and other activities. The activities of the Prosperous Family Income Improvement Group are also not yet implemented, where the activity is expected to empower the village community economically. Cross-sectoral activities have also not been implemented and coordinated well, it seems that there is no program that can be felt directly even though the commitment at the beginning of the declaration has been carried out.